Voice transmission through WiFi. (10th May 2019) - Goel, Shalini; Garg, Vipul; Garg, Deepak; Kathait, Manshiv
In an era of digital communication, one of the key requirements is of free connectivity. In addition, one of the most anticipated issues is poor connectivity in most of the areas and it is not possible to install infrastructure-based networks due to cost-effectiveness or non-vulnerability terrains (cellular blind spots like a desert, battlefields, forests, etc.). In the light of the above-mentioned discussion, an android application has been developed in the ongoing project for Android-based wireless devices named WiFi_Intercom. WiFi_Intercom uses classes which allow its user to connect with other connected users through WiFi wireless standard using point to point (P2P) or WLAN connection as a means of communication between Android-based wireless devices. The application will also allow the mobile user to search and call other connected users within the WiFi range through the application. Each mobile device connects to a WLAN router and identifies itself in the routing table.